Use of Underground Mining Activities in Earthquake Search and Rescue Works: Use of Underground Mining Activities in Earthquake Search and Rescue Works - Sırrı Sargın, Süleyman; Şensöğüt, Cem (International Journal of Economic and Environmental Geology, 2023)
Although the mining sector has the task of providing raw materials directly or indirectly to industrial establishments, it unfortunately contains great dangers and risks for its employees in terms of occupational health and safety. Especially in mining enterprises operating underground, roof collapse, sudden gas discharge, flooding, gas explosions etc. negativities that occur during production cause great material and moral destruction. In such big problems, well-trained rescue teams of mines play an important role in saving the lives of many miners. Earthquake disasters affecting 11 provinces in Turkey caused great destruction, many people died in building debris and collapses, and buildings and industrial facilities were severely damaged on Feb. 6 2023. In the search and rescue works that started after the earthquake, the outstanding efforts of the underground mine workers in the field and the methods they used in these studies attracted the attention of the public. In this study, evaluations were made by giving some underground rescue methods used in search and rescue activities in the Adıyaman earthquake region which is one of 11 provinces affected by the disaster in Turkey. Keywords: Underground mining, hazards and risks, earthquake, search and rescue.